TRAINING IN THE USE OF THE QUIZIZZ APPLICATION FOR IMPRESSIVE AND MODERN ONLINE LEARNING FOR THE Z GENERATION - Jane Elnovreny (Yayasan Education and Social Center, 2021)
Generation Z, also known as the